If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1n-4n+3=-30
We move all terms to the left:
1n-4n+3-(-30)=0
We add all the numbers together, and all the variables
-3n+33=0
We move all terms containing n to the left, all other terms to the right
-3n=-33
n=-33/-3
n=+11
| 7=2x+4x+16 | | 3(5b+6)=-102 | | 155=2x | | w+1.4=5.72 | | X+3=4x+11 | | 4(5-5a)=-100 | | 90=6(4m-1) | | -8+5(x-8)+2x=-10 | | -140-15=5(5+9b) | | 9.95-0.7z=-9.85-4.3z | | (-2)(x)=-2x* | | -4-5(1-4m)=71 | | 6(x-2)+12=18 | | 4y-6=2y+40 | | 8p-6=-2(-4p+1) | | 3=p−91/2 | | 3(2x-8)-7=-73 | | 4x^2=53.3*(0.5-x)^2 | | -112=4(-3+5z) | | 2.5(6.25x+0.5)=11 | | 10-10p=-8-10+4p | | 59=9+5y | | (3)(x)=2x | | 34x–68=0 | | 11x=-9+2+x=-199 | | -5c-6=-8c+6 | | b8=5 | | 3×x+53=11 | | 5x-2(3x+6)=5x-2(3x+5) | | q+69=81 | | (-4)(x)=(1/2)x+1 | | 10x-5(x-2)=20 |